Using mathematical models to evaluate germination rate and seedlings length of chickpea seed (Cicer arietinum L.) to osmotic stress at cardinal temperatures - Shah, Sikandar; Ullah, Sami; Ali, Sajjad; Khan, Ajmal; Ali, Muhammad; Hassan, Said (PloS one, 2021)
Cicer arietinum is the 3 rd most important cool season legume crop growing in vast arid and semi-arid regions of the world. A lab experiment was designed using hydrothermal time model (HTT) to investigate the chickpea seed germination (SG) behavior, cardinal temperatures and germination responses across fluctuating temperatures ( T s ) and water potentials ( Ψ s ). Seeds of chickpea var. NIFA 1995 were germinated at six constant T s (7, 14, 21, 28, 35 and 42°C) each having the following five water potentials: 0, -0.2, -0.4–0.6 and -0.8 MPa. Germination percentage (G%) decreased significantly at (* P ≤ 0.05) from 86.7% at 28°C in -0.2 MPa to 10% in -0.2 MPa at 7°C. The germination rate (GR = 1/t 50 ) against different T percentiles exhibited that linear increase was observed in the GR pattern above and below the T o. Based on the confidence intervals of the model coefficients and ( R 2 : 0.96), the average cardinal temperatures were 4.7, 23 and 44.2°C for the base ( T b ), optimal ( T o ) and ceiling ( T c ) temperatures respectively. θT 1 value was observed maximum at 28°C in -0.2 MPa and decreases with decreasing Ψ (-0.8 MPa). In comparison with control, the θT 2 value was also highest in -0.2 MPa at 28°C. The thermal time (TT) concept is well fitted to germination fraction data in distilled water with an R 2 value increasing 0.972. The hydro time constant ( θ H) increased with an increase in T to T o and then decreased when T > T o . The ѱ b(50) irregularly varied with increasing T , σ Ψ b was also recorded lowest (0.166 MPa) at 28°C and highest (0.457 MPa) at 7°C. Based on the statistical analysis, cardinal temperatures, hydrothermal time constant ( θ HTT) and germination findings the HTT gives an insight into the interactive effect of T and Ψ on seed germination time courses under varying environmental conditions.